2017
DOI: 10.1111/apa.13859
|View full text |Cite
|
Sign up to set email alerts
|

Using a standardised protocol was effective in reducing hospitalisation and treatment use in children with newly diagnosed immune thrombocytopenia

Abstract: Aim: Childhood immune thrombocytopenia (ITP) has been associated with low bleeding rates and a high frequency of spontaneous remission. Although current guidelines suggest that most patients are just observed, children still receive platelet-enhancing therapies for fear of bleeding complications. We hypothesised that a standardised protocol with a stepdown approach would reduce hospitalisation and treatment use.Method: A retrospective chart review was performed on patients diagnosed with acute ITP between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Finally, methodologically, they attempted to apply Buchanan bleeding scores to the patients during the retrospective chart review, whereas we chose a simpler approach to defining UT that mirrored our treatment guideline. 4 There were several barriers to implementation. The most significant barrier was physician past experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, methodologically, they attempted to apply Buchanan bleeding scores to the patients during the retrospective chart review, whereas we chose a simpler approach to defining UT that mirrored our treatment guideline. 4 There were several barriers to implementation. The most significant barrier was physician past experience.…”
Section: Discussionmentioning
confidence: 99%
“…There are rare single-center examples of successful reduction in aITP treatment by changing inpatient provider practice. 4,5 However, these success stories have not led to broad practice change. Pediatric Health Information System (PHIS) data revealed that .90% of children with aITP presenting to freestanding children' s hospitals are treated despite only 14% having bleeding symptoms.…”
mentioning
confidence: 99%
“…Although current guidelines suggest that most patients are just observed, children still receive platelet-enhancing therapy because of concerns about complications related to bleeding. Labrosse et al report that introducing a standardised protocol with a step-down approach reduced hospitalisation and the length of prednisolone treatment in children with newly diagnosed ITP, without any increase in disease complications (9). Ljung comments on the findings (10).…”
Section: Using a Standardised Protocol Reduced Hospitalisation For Chmentioning
confidence: 99%
“…The modification increased the notreatment percentage of this milder subgroup from 40 to 74%. Like the paper of Labrosse et al above (9), it shows that it is worthwhile to modify and present consensus data from extensive more academic guidelines to a more userfriendly format for the clinician. Hopefully, such papers will stimulate the creation of local guidelines and flow-sheets to better help the paediatrician choose the recommended noninterventional approaches when these are indicated.…”
mentioning
confidence: 96%
“…It is in the context that the recent paper by Labrosse et al published in Acta Paediatrica should be discussed (9). This paper presents the experience of a standardised protocol flow sheet, with a step-down approach to guide decisions on hospitalisation and treatment of ITP in children.…”
mentioning
confidence: 99%